Holocaust survivors : resettlement, memories, identities - Ofer, Dalia; Ouzan, Francoise S.; Baumel-Schwartz, Judy Tydor (Berghahn Books, 2012)
Many books on Holocaust survivors deal with their lives in the Displaced Persons camps, with memory and remembrance, and with the nature of their testimonies. Representing scholars from different countries and different disciplines such as history, sociology, demography, psychology, anthropology, and literature, this collection explores the survivors' return to everyday life and how their experience of Nazi persecution and the Holocaust impacted their process of integration into various European countries, the United States, Argentina, Australia, and Israel. Thus, it offers a rich mix of pe.